ORGANIZATIONAL JUSTICE AS A FRAMEWORK FOR UNDERSTANDING UNION‐ MANAGEMENT RELATIONS IN EDUCATION - Poole, Wendy (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
In this article, I have conceptualized union‐management relations using an organizational justice framework. I consider organizational justice theory, including distributive, procedural, interactional, and what I call relational justice perspectives. Utilizing examples from my experience and research, I illustrate and discuss various forms of organizational justice operating in school systems and influencing teachers’ perspectives and union actions. I urge researchers and practising educational leaders to use an organizational justice perspective to better understand teachers’ per‐ spectives and union‐management relations in education. Key words: teacher identity, educational leadership, teacher unions, school leadership, board‐teacher relations, government‐teacher relations, relational justice Dans cet article, l’auteure analyse les relations patronales‐syndicales à l’aide d’un cadre axé sur la justice organisationnelle. Elle fait appel à des théories sur la justice organisationnelle, notamment les théories sur la justice distributive, procédurale et interactionnelle, et à ce qu’elle appelle la justice relationnelle. À l’aide d’exemples tirés de son expérience et de ses recherches, elle illustre et analyse diverses formes de justice organisationnelle à l’œuvre dans des systèmes scolaires et ayant une influence sur les points de vue des enseignants et les actions des syndicats. Elle incite fortement les chercheurs et les leaders dans le monde de l’éducation à adopter le point de vue de la justice organisationnelle afin de mieux comprendre les points de vue des enseignants et les relations patronales‐syndicales dans les milieux de l’enseignement. Mots clés : identité des enseignants, leadership et éducation, syndicats d’enseignants, direction d’école, relations entre la commission scolaire et les enseignants, justice relationnelle